2022
DOI: 10.1039/d1nr07670a
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of lung cancer via biointerference-free, target microRNA-triggered core–satellite nanocomposites

Abstract: MicroRNAs (miRNAs) are emerging as essential liquid biopsy markers for early cancer detection. Currently, the clinical applications of miRNAs still lag behind due to their high sequence similarity and rarity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Other efforts of using miRNA-based liquid biopsy for lung cancer early detection were made by using single miRNAs as biomarkers such as miR-17-19 [31], miR-20 [32], miRNA-21 [33][34][35][36][37][38][39][40][41][42], miR-25 [43], miR-29 [44], miR-30 [45], miR-31 [46], miR-125, miR-126 [47][48][49], miR-135 [50], miR-143 [51], miR-145 [32], miR-148/152 family [52], miR-153, miR-155 [36,53,54], miR-182, miR-183 [47], miR-185 [55], miR-184 [56], miR-200 [57], miRNA-210 [47,58], miR-221 [32], miR-223 [32,59], miR-328 [60], miR-339 [61], miR-411 [62], miR-486 [63], miR-499 [64], miR-519 [65], miR-770 [66], mi-R762 [67], microRNA-2355 [68], hsa-miR2116, hsa-miR449c and hsa-miR2117 [69]. These single biomarker-based approaches led to similar results, but the heterogeneity of the study and the lack of a validation...…”
Section: Micro Rnas (Mirnas)mentioning
confidence: 99%
“…Other efforts of using miRNA-based liquid biopsy for lung cancer early detection were made by using single miRNAs as biomarkers such as miR-17-19 [31], miR-20 [32], miRNA-21 [33][34][35][36][37][38][39][40][41][42], miR-25 [43], miR-29 [44], miR-30 [45], miR-31 [46], miR-125, miR-126 [47][48][49], miR-135 [50], miR-143 [51], miR-145 [32], miR-148/152 family [52], miR-153, miR-155 [36,53,54], miR-182, miR-183 [47], miR-185 [55], miR-184 [56], miR-200 [57], miRNA-210 [47,58], miR-221 [32], miR-223 [32,59], miR-328 [60], miR-339 [61], miR-411 [62], miR-486 [63], miR-499 [64], miR-519 [65], miR-770 [66], mi-R762 [67], microRNA-2355 [68], hsa-miR2116, hsa-miR449c and hsa-miR2117 [69]. These single biomarker-based approaches led to similar results, but the heterogeneity of the study and the lack of a validation...…”
Section: Micro Rnas (Mirnas)mentioning
confidence: 99%
“…Lung cancer: Raman reporter-conjugated silver wrapped gold nanorods functionalized with DNA probes for the detection of lung cancer-related microRNAs, miRNA-21, in complex plasma samples have been studied [79]. Through a hybridization-based recognition effect, a large SERS signal enhancement caused by miRNA-21-triggered assembly of core-satellite nanocomposites was observed.…”
Section: Gold Nanoparticles For Cancer Imaging Using Sersmentioning
confidence: 99%
“…The nanocomposites enabled the sensitive detection of miRNA-21 in quantities as low as 0.1fM in a linear range of 10fM to 1nM. Detection of miRNAs is historically difficult, however, this platform provides bio-interference-free, quantitative, and direct SERS imaging of cancer without RNA pre-extraction, thereby demonstrating clinical potential for the selective, sensitive, and accurate quantification and detection of miRNA markers in liquid biopsy samples [79].…”
Section: Gold Nanoparticles For Cancer Imaging Using Sersmentioning
confidence: 99%
“…Recently, Cairou Chen and collaborators developed target-triggered core-satellite nanocomposites made of gold nanorods and 4-sulfanylbenzonitrile for the surface-enhanced Raman spectroscopic detection of miRNA-21 (an oncogenic miRNA expressed in mammalian cells associated with various cancer types). 43 Likewise, a gold-nanoparticle-oxidized multiwalled carbon nanotube composite is used as an electrochemiluminescence immunosensor to detect carcinoembryonic antigens. 44 The authors suggested that although the detection sensitivity is lower, exploring this avenue can open up possibilities in developing highly sensitive immunosensors for the detection of carcinogenic antigens.…”
Section: Metal Nanosystemsmentioning
confidence: 99%